Motivational reasons associated with the participation of registered nurses in the nursing degree program - Coomarasamy, Jeya Devi (1998)
The nursing degree program is becoming popular among the registered nurses in Malaysia. This is despite the fact that most organisations do not make it a compulsory criterion for upward mobility or promotion. Therefore, it is important for nursing educators or HRD managers to understand why registered nurses participate voluntarily in the nursing degree program. The purpose of this study is to identify the motivational reasons influencing the participation of registered nurses in the program. It is aimed to determine: (1) the major reasons for participation in the nursing degree program; (2) the differences in motivational reasons for participation between registered nurses in clinical, management and teaching positions; (3) the relationship between selected personal, professional and organisational variables and the reasons for participation and (4) whether nurses doing the program full time had different reasons for participation compared to nurses doing the program part time.The study was based on a descriptive / correlational design and employed a survey methodology. The instrument used was the four-section questionnaire: personal, professional, organisational data and the 30 statement Participation Reasons Scale. A total of 107 valid responses was analysed. The highest ranked statement was centered around the maintainance of professional competence. The above findings support existing studies where professional knowledge and skills were found to be the strongest motivators. The predetermined factor which had the highest average mean score was Professional Improvement and Development, followed by Professional Service, Professional Commitment and Reflection, Collegial Learning and Interaction and Personal Benefits and Job Security. There were no significant relationships between selected personal, professional and organizational variables with reasons for participation. However, a significant difference in relationship was found between nurses doing the program full time and part time with one participation factor - Professional Service. Further analysis showed that the Nursing Sisters doing the program part time had low mean scores for reasons associated with Professional Service compared to the other group of nurses. This requires further research to determine the underlying reasons behind it. The study findings indicate that registered nurses were highly motivated towards the nursing degree program. It is highly recommended that HRD managers and educators take advantage of this current positive behaviour. Attempts should be made to increase the accessibility and availability of degree opportunities for nurses while maintaining the credibility of the program.